Analysis of outcomes for children examined in the outpatient clinic of tertiary care pediatric institution due to loss of consciousness - Peličić, Milena (Medicinski podmladak, 2025)
:Introduction Loss of consciousness is a common anamnestic data in pediatric outpatient clinics. :Aim To determine the outcome for children who were examined due to loss of consciousness in the outpatient clinic of a tertiary care pediatric institution during a two and a half month period.:Material and methods A retrospective study was conducted. Data were obtained from the medical records of the outpatient department in the Institute for Mother and Child Protection of Serbia "Dr. Vukan Čupić", in the admission period from September 3 until November 17 2022. Considered data were: gender, age, referral and discharge diagnosis, nature of the seizure on admission, associated complaints and comorbidities, conducted EEG (electroencephalography) and CT (computerized tomography) /MRI (magnetic resonance imaging), prescribed therapy and outcome. All data were processed in SPSS v21.:Results The study included 97 patients (50 male and 47 female) with an average age of 96 months. The most common referral diagnosis were unclassified convulsions (33%), and discharge diagnosis was syncope (32%). In 49.5% of cases, seizures were reported as the first episode. Elevated body temperature, as the most common associated symptom, was present in 32% of patients. Comorbidities were found in 10.3% of patients. Regarding the outcome, 49.5% of patients were referred for home treatment, 46.4% were hospitalized, 2% were referred for subspecialty examination. Therapeutically, advice was most often given for syncope (37%), while Diazepam or Midazolam were most often prescribed medicines to stop seizure (27.1%). EEG was performed in 10.3% of patients, of which 3.1% were normal and 4.1% pathological findings. CT/MRI scans were performed in 9.3% of patients and all had normal findings.:Conclusion The majority of children who experience loss of consciousness have a favorable outcome – complete recovery, without neurological deficits and complications, and are discharged home without continuous therapy, with advice for preventing the recurrence of complaints.:Keywords loss of consciousness, convulsions, febrile seizure, syncope, epilepsy
Keywords: loss of consciousness; convulsions; febrile seizures; syncope; epilepsy